Etnosaberes geométricos presentes na produção de trabalhadores de chapéus de couro: um estudo etnomatemático em Nossa Senhora da Glória-SE - Ângelo, Mateus Santos (2025)
This study aimed to analyze, through the lens of the Ethnomathematics Program, how the geometric ethnoknowledge of workers involved in leather hat production in the municipality of Nossa Senhora da Glória-SE is culturally constructed. The research sought to answer the question: How is the geometric ethnoknowledge of workers involved in leather hat manufacturing in Nossa Senhora da Glória-SE culturally constructed? The theoretical foundation was based on ethnomathematical studies, focusing on the works of Ubiratan D’Ambrósio and Knijnik. Methodologically, the work was configured as an ethnographic study with a qualitative approach, conducted through data collection based on narrative autobiographies, semi-structured interviews, and participant observation. The investigation involved five workers residing in the São Clemente Village (Vila do Padre) in Nossa Senhora da Glória-SE, aged between 33 and 97 years. The results revealed that the geometric knowledge, or "ticas de matema," employed in hat production is acquired empirically and transmitted orally from generation to generation. The ethnoknowledge manifests itself in the practical use of geometric figures and concepts, even if the workers do not formally name them. Practices involving measurement and numbering of shapes were highlighted: the use of hand fingers as a unit of measurement to calibrate the compass opening, and visual assessment ("volume" or "by eye") to determine the size of the mold. Plane and Spatial Geometry: The construction of the "brim" involves using a handmade compass to trace concentric circles, and the assembly process of the crown represents the transformation from plane to space (two to three dimensions). Symmetry and Polygons: Reflective symmetry is present in the crown model, and the "engarração" process (thickening the brim) and the "snail" stitching pattern involve fitting figures such as triangles, trapezoids, rectangles, rhombuses, and squares. The research concluded that the geometric ethnoknowledge of these artisans is culturally constructed knowledge that is effective for everyday practices. The identification and appreciation of these "ticas de matema" can serve as methodological alternatives for teaching geometry, allowing teachers to work with geometric concepts in a more meaningful and contextualized way, in addition to overcoming the lag in the development of students' geometric thinking.